Strategi Pengelolaan Wisata Sungai Brayeun dalam Meningkatkan Ekonomi Masyarakat Lokal - Agustina, Lisa; Fitriani, Fitriani; Anwar, Anwar; Abubakar, Abubakar; Afni, Nur; Fatianda, Septian; Irwan, Irwan (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Tourism is one of the strategic sectors that can drive economic growth, especially in rural areas that have unique natural and cultural potential. Brayeun River, located in Leupung District, Aceh Besar Regency, is a natural tourist destination that offers panoramic river views, the natural charm of the mountains, as well as various interesting activities for swimming and environmentally-based educational tours.This research aims to find out the management strategy of the Brayeun River tourist attraction in increasing the economic income of the local community and the impact received by the community from managing the potential of the tourist attraction. The Brayeun river tourism management strategy is an alternative to sustainable development that involves the community as a driving factor by utilizing the natural potential that exists in the surrounding environment. In this study, using qualitative research methods with the aim of observing the phenomenon of the management strategy of the Brayeun river natural tourist attraction in increasing the economic income of local communities. The data collection techniques through the stages of observation, interviews and documentation as well as analysis of the data found during the research process. The results showed that the more tourists who visit the Brayeun River tourist attraction destination, the greater the potential for economic growth of the local community. In addition, this positive impact also provides good benefits such as the construction of village roads, as well as the opening of jobs for the local community. With targeted management, Brayeun River tourism has the potential to become a sustainable driver of the local economy.